Location of industry and international competitiveness - Hirsch, Seev. (Oxford : Clarendon Press, 1967)
This book shows a strong competitive position on the proposition that a country which has a strong competitive position in a given industry at a given time may lose this position when character of the industry changes.
Based on the author's thesis Harvard, Graduate School of Business Administration, 1965. It has footnotes
Includes bibliographical footnotes and index.
mf 25/01/2019
Loans
Keywords: Commerce; Industrial location; Export marketing; Electronic industries